THE EFFECT OF RED BETEL LEAF EXTRACT (Piper crocatum) ON THE LIVER HISTOPATHOLOGY OF WHITE RATS (Rattus norvegicus) INDUCED BY ALLOXAN - Esther Daniella Pidu Dimu; Efrisca Br. Meliyuita Damanik (Cendana Medical Journal, 2025)
Abstract Introduction:Diabetes mellitus is a metabolic disease characterized by hyperglycemia, which results from decreased insulin secretion, impaired insulin action, or both. This condition can lead to the formation of Reactive Oxygen Species (ROS. Red betel leaf contains saponins, flavonoids, alkaloids, and tannins, which act as antioxidants. Methods: This study was a laboratory experimental research using a true experimental design with a posttest-only control group approach. The samples were divided into five groups: negative control, positive control, treatment 1 (150 mg/kgBW), treatment 2 (250 mg/kgBW), and treatment 3 (350 mg/kgBW). Data were analyzed using the Kruskal-Wallis test followed by the Post Hoc Tukey HSD test. Results: The Kruskal-Wallis test showed a significant difference in the liver histopathology of white rats induced with alloxan after administration of red betel leaf extract, with a p-value of 0.002 (p < 0.05). Discussion: The administration of red betel leaf extract proved to have positive effect on improving liver histopathology in alloxan-induced rats, with the most effective result observed at a dose of 350 mg/kgBW, showing nearly normal liver cell structures. Conclusion: Red betel leaf extract has significant effect on the liver histopathology of alloxan-induced white rats (Rattus norvegicus), with the most effective dose being 350 mg/kgBW.